Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 6 - Review Exercises - Page 291: 7



Work Step by Step

RECALL: $y=\tan^{-1}{x} \longrightarrow \tan{y}=x$ Note that $\tan {(\frac{\pi}{3})}=\sqrt3$. Since tangent is an odd function, $\tan{(-x)}=-\tan{x}$. Thus, $\tan{(-\frac{\pi}{3})}=-\tan{(\frac{\pi}{3})}=-\sqrt3$ Therefore, $y=\tan^{-1}{(-\sqrt3)}\longrightarrow y=-\frac{\pi}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.